Cinematic strategies against silenced and repressed past a formal analysis of unconventional films from Turkey in the 2000s - Büyükgöze, Selime (İstanbul Bilgi Üniversitesi, 2018)
This thesis focuses on the relation between memory and cinema in the context of cinema in Turkey. It analyses the unconventional films made between 1999 and 2014 during a period of political transformation which engage with the various traumatic events in the history of Turkey. It is argued that the formal strategies used in these films constitute a film language that enables representing both the silenced and repressed past and how the past is being lived and sustained in the present, and that this language engages with discussions of memory in Turkey. Memory is the core analytical tool in this thesis, and it is discussed with its collective aspects. The films analyzed in this thesis are discussed in terms of their postmemorial function. The selected films are situated into the corpus of cinema in Turkey, and their transnational characteristics are indicated. Considering the filmmakers’ critical positions to the hegemonic discourses and national identity in Turkey, these films are situated into the accented cinema literature. The accented style is used as a critical and formal guideline to analyze the films. Thematic preoccupations, the use of epistolary form and spatial relations in the selected films are closely examined in order to understand the film language that emerges in these films as a response to the forced silence and repression of the past. Structures of feeling and truth claiming in these films are discussed in terms of memory activism in Turkey. Throughout this thesis, it is argued that these films produce aesthetic responses to the political discourses, and contribute to the demand for coming to terms with the past.

Bu tez Türkiye’deki sinema bağlamında hafıza ve sinema arasındaki ilişkiye odaklanmaktadır. Siyasi bir dönüşüm sürecinde, 1999 ve 2014 yılları arasında yapılmış, Türkiye tarihindeki çeşitli travmatik olaylarla ilişkilenen konvansiyonel olmayan filmleri inceler. Bu filmlerde kullanılan biçimsel stratejilerin bastırılmış ve sessizleştirilmiş geçmiş ile bu geçmişin bugünde nasıl yaşandığını ve sürdürüldüğünü temsil etmeye olanak tanıyan ve Türkiye’deki hafıza tartışmaları ile ilişkilenen bir film dili oluşturduğu iddia edilmiştir. Hafıza bu çalışmanın temel analitik aracıdır ve kolektif yönleriyle tartışılmıştır. Bu tezde analiz edilen filmler hafıza sonrası işlevleri ile tartışılmıştır. Seçilen filmler Türkiye’deki sinema külliyatı içerisinde konumlandırılmış ve ulus aşırı nitelikleri belirtilmiştir. Yönetmenlerin Türkiye’deki hegemonik söylem ve ulus kimliğine eleştirel pozisyonları göz önüne alınarak bu filmler aksanlı sinema literatürü içinde konumlandırılmıştır. Aksanlı stil filmleri incelerken eleştirel ve biçimsel bir kılavuz olarak kullanılmıştır. Seçilen filmlerdeki tematik ortaklıklar, mektup formunun kullanımı ve mekânsal ilişkiler, geçmişe dair zorunlu sessizlik ve baskıya cevap olarak gelişen film dilini anlamak için detaylı incelenmiştir. Bu filmlerdeki duygu yapıları ve hakikat talebi Türkiye’deki hafıza aktivizmi açısından tartışılmıştır. Tez boyunca, bu filmlerin siyasi söylemlere estetik cevap ürettikleri ve geçmişle yüzleşme talebine katkı yaptıkları iddia edilmiştir.
Sessizleştirilmiş ve bastırılmış geçmişe karşı sinematik stratejiler: 2000'lerin Türkiye'sinden konvansiyonel olmayan filmlerin biçimsel analizi
Keywords: Memory; Trauma; Film Form; Cinema In Turkey; Accented Cinema; Hafıza; Travma; Film Biçimi; Türkiye’de Sinema; Aksanlı Sinema